2006
DOI: 10.1096/fj.06-6899com
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in fast skeletal troponin I, troponin T, and β‐tropomyosin that cause distal arthrogryposis all increase contractile function

Abstract: Distal arthrogryposes (DAs) are a group of disorders characterized by congenital contractures of distal limbs without overt neurological or muscle disease. Unexpectedly, mutations in genes encoding the fast skeletal muscle regulatory proteins troponin T (TnT), troponin I (TnI), and beta-tropomyosin (beta-TM) have been shown to cause autosomal dominant DA. We tested how these mutations affect contractile function by comparing wild-type (WT) and mutant proteins in actomyosin ATPase assays and in troponin-replace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
66
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(73 citation statements)
references
References 55 publications
6
66
0
1
Order By: Relevance
“…This could suggest that these specific DA mutations cause congenital contractures on the basis of hypercontractility and increased tension in developing fast twitch skeletal muscles, resulting in diminished muscle movement in utero. The possibility that PIEZO2 senses forces associated with muscle contraction, combined with the finding that mutant PIEZO2 proteins have increased activity, is likewise consistent with the view that the integrated development of muscles and joints during embryogenesis is an active rather than a passive process (13). For example, increased ion flux could result in increased neural firing during fetal muscle movement, and this in turn could inhibit overall muscle movement via a negative feedback loop that integrates muscle contraction and movement.…”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…This could suggest that these specific DA mutations cause congenital contractures on the basis of hypercontractility and increased tension in developing fast twitch skeletal muscles, resulting in diminished muscle movement in utero. The possibility that PIEZO2 senses forces associated with muscle contraction, combined with the finding that mutant PIEZO2 proteins have increased activity, is likewise consistent with the view that the integrated development of muscles and joints during embryogenesis is an active rather than a passive process (13). For example, increased ion flux could result in increased neural firing during fetal muscle movement, and this in turn could inhibit overall muscle movement via a negative feedback loop that integrates muscle contraction and movement.…”
Section: Resultssupporting
confidence: 70%
“…Interestingly, previously identified DA mutations reside in MYH3 and MYH8 that encode sarcomeric proteins, or in TNNI2, TNNT3 and TPM2, respectively (2,(12)(13)(14). These proteins are expressed in fast twitch fibers, and functional studies have shown that DA (DA1 and DA2) mutations in TNNI2, TNNT3, and TPM2 produce increased contractile function in troponinreplaced rabbit psoas fibers (13).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This temporal expression pattern supports a theory that congenital contractures may result from a period of fetal akinesia [14]. However, recent in vitro evidence suggests human mutations in TNNT3, TNNI2, and TPM2 increase the contractility of fast-twitch muscle fibers [19], with the result being that the contracture forms because of excess contractility. Muscle abnormalities limited to the fetal period are consistent with the natural history of most cases of successfully treated idiopathic clubfoot, in which the contracture does not recur and the foot demonstrates minimal weakness [6].…”
Section: Introductionsupporting
confidence: 75%
“…Similarly, the results from in vitro contractility studies in which recombinant mutant TnI and b-tropomyosin 34 molecules were used suggest that distal arthrogryposis syndromes are, in some cases, caused by increased myofiber contractility. However, the mechanism by which contractility is altered is not yet clear 35 . In contrast, direct measurement of the contractile properties of chemically skinned single muscle fibers sampled from affected muscles in individuals with MYH3 mutations suggests that maximal force normalized to fiber cross-sectional area is less than that observed in myofibers from unaffected individuals (Bamshad and Beck, unpublished data).…”
Section: Tpm2 a Gene That Encodes Tropomyosin 2 (Bamshad Unpublishementioning
confidence: 99%